Intraoperative Neurophysiologic Assessment in Deep Brain Stimulation Surgery and its Impact on Lead Placement - Krauss, Philipp; Oertel, Markus Florian; Baumann-Vogel, Heide; Imbach, Lukas; Baumann, Christian Rainer; Sarnthein, Johannes; Regli, Luca; Stieglitz, Lennart Henning (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objectives While the efficacy of deep brain stimulation (DBS) to treat various neurological disorders is undisputed, the surgical methods differ widely and the importance of intraoperative microelectrode recording (MER) or macrostimulation (MS) remains controversially debated. The objective of this study is to evaluate the impact of MER and MS on intraoperative lead placement.Patients and Methods We included 101 patients who underwent awake bilateral implantation of electrodes in the subthalamic nucleus with MER and MS for Parkinson's disease from 2009 to 2017 in a retrospective observational study. We analyzed intraoperative motor outcomes between anatomically planned stimulation point (PSP) and definite stimulation point (DSP), lead adjustments and Unified Parkinson's Disease Rating Scale Item III (UPDRS-III), levodopa equivalent daily dose (LEDD), and adverse events (AE) after 6 months.Results We adjusted 65/202 leads in 47/101 patients. In adjusted leads, MS results improved significantly when comparing PSP and DSP (p < 0.001), resulting in a number needed to treat of 9.6. After DBS, UPDRS-III and LEDD improved significantly after 6 months in adjusted and nonadjusted patients (p < 0.001). In 87% of leads, the active contact at 6 months still covered the optimal stimulation point during surgery. In total, 15 AE occurred.Conclusion MER and MS have a relevant impact on the intraoperative decision of final lead placement and prevent from a substantial rate of poor stimulation outcome. The optimal stimulation points during surgery and chronic stimulation strongly overlap. Follow-up UPDRS-III results, LEDD reductions, and DBS-related AE correspond well to previously published data.
Keywords: DBS; deep brain stimulation; intraoperative neurophysiology; neuromodulation; Parkinson's disease